Studi Nilai Konseling Islam dalam Buku Nasehat Siti Budiman Karya Sulaiman Ar-Rasuli - Masnur Al Shaleh; Diana , Raden Rachmy; Triasa , Arif Rahmat (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2024)
One of the Minangkabau cultural products that contains Islamic counseling values is the advice book Siti Budiman by Sulaiman Ar-Rasuli. The book describes the educational process in a family environment that seeks to instill good morals by parents to children. This discussion is increasingly important to explore, given the high level of juvenile delinquency in Minangkabau or West Sumatra, which is an administrative area in Indonesia. This article will comprehensively analyze the biography of Sulaiman Ar-Rasuli. As well as, the purpose, objectives, elements, principles, and values of Islamic counseling. The results of this study found ideas in the form of advice written by Sulaiman Ar-Rasuli related to the affirmation of faith and ideal Islamic law in Minangkabau.